2018
DOI: 10.1016/j.jamcollsurg.2017.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Signature Panels and Breast Cancer Therapy: Patterns of Use and Impact on Clinical Decision Making

Abstract: Use of MSPs among patients with breast cancer has increased over time and is associated with a decreased use of adjuvant chemotherapy. Oncotype DX continues to be the most widely used MSP, although MP use has increased over time. Future studies are warranted to determine the optimal use of these MSPs in risk assessment and postoperative decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Gene signatures are currently being used in clinical practice. Two examples are Oncotype DX [13][14][15], which provides a breast cancer recurrence score based on expression of 21 genes, and Coloprint, which provides a colon cancer recurrence score based on expression of 18 genes [16][17][18]. Results obtained with these assays have shown that screening new prognostic cancer markers based on gene expression profiles is a promising high-throughput molecular identification method.…”
Section: Discussionmentioning
confidence: 99%
“…Gene signatures are currently being used in clinical practice. Two examples are Oncotype DX [13][14][15], which provides a breast cancer recurrence score based on expression of 21 genes, and Coloprint, which provides a colon cancer recurrence score based on expression of 18 genes [16][17][18]. Results obtained with these assays have shown that screening new prognostic cancer markers based on gene expression profiles is a promising high-throughput molecular identification method.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have explored the prognostic role of gene signatures in predicting the outcome of HCC. The effect of clinical practice based on gene expression profiles has shown that gene signatures might be a promising high-throughput molecular identification method [22][23][24]. In that regard, Liu et al [25] identified a four-gene metabolic signature and Xiang et al [26] identified seven-senescence-associated gene signature for predicting OS in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some gene signatures have been used in clinics, such as multigene signature panels (MSPs) to evaluate breast cancer recurrence [19], which reveals that it is a reliable molecular identi cation method to screen gene prognostic biomarkers by gene expression pro ling. Lin et al constructed a prognostic model for CC patients undergoing radiotherapy and chemotherapy with stage IB-IV based on magnetic resonance imaging (MRI), whole-tumor apparent diffusion coe cient (ADC), human papillomavirus (HPV) genotyping [20].…”
Section: Discussionmentioning
confidence: 99%